Theory of Everything - Unification (Global Journal of Science Frontier Research, 2020)
Quantum Mechanics and Relativity are undoubtedly the two major pillars of Modern Physics. In this paper, I present an official unification of both major twin pillars with the "Theory of Everything" (TOE) which I discovered in (2019). Uniting both major pillars will in turn unite other areas of physics and display the physics of the dark dimension.
Keywords: theory of everything; relativity; quantum mechanics; dark energy; energy; spacetime